Serous carcinoma of the uterine cervix: Clinicopathological features differing from serous carcinomas of other female organs. Issue 1 (22nd October 2019) - Kitade, Shoko; Ariyoshi, Kazuya; Taguchi, Kenichi; Maenohara, Shoji; Tomita, Yui; Sonoda, Kenzo; Okadome, Masao; Saito, Toshiaki
Abstract: Aim: Serous carcinoma of the uterine cervix (USCC) is a very rare malignant tumor, while this histological subtype is common in the ovary, fallopian tube, uterine corpus and peritoneum. Because of its rarity, details of the clinicopathological features of USCC are largely unknown. We retrospectively analyzed the clinicopathological characteristics of five cases of pure USCC. Methods: We reviewed the medical records and pathological specimens of five USCC cases who were treated at the Gynecology Service of the National Hospital Organization Kyushu Cancer Center, Japan, between 2000 and 2017. The clinicopathological features were also compared with those of serous carcinomas of the endometrium and ovary who were treated during the same period. Results: Five patients were treated at our hospital between 2000 and 2017. Three tumors were stage IB1, one was stage IIB, and one was stage IVB. The median follow‐up time was 104 months (range 26–210). Four patients other than stage IVB were treated with radical hysterectomy and have been free of relapse. One patient with stage IVB tumor was treated with platinum‐based combination chemotherapy and is currently on maintenance therapy with bevacizumab and remains free of relapse. Conclusion: USCC has a distinctive clinicopathological feature that differentiates it from serous carcinomas of other female organs. USCC had been thought to be a poor prognostic disease; however, it could be curable if it is not accompanied by lymph node metastasis or peritoneal dissemination. We might conquer USCC even if it is accompanied by lymph node metastasis with the use of multimodal therapy.